The Uncommercial Traveller - Dickens, Charles, 1812-1870 (Salt Lake City, UT : Project Gutenberg, 1997)
"The Uncommercial Traveller" by Charles Dickens is a collection of literary sketches published between 1860-1861. Adopting the persona of a wandering observer, Dickens documents his explorations through Victorian London and beyond, traveling "for the great house of Human Interest Brothers." These articles blend reportage, character studies, and social commentary, revealing both everyday street life and hidden aspects of society. His nocturnal wanderings and investigations$1 (Bfrom shipwrecks to workhouses$1 (Bshowcase his characteristic wit, humor, and concern for the poor and oppressed. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Uncommercial_Traveller
Release date is 1997-05-01
David Price
Keywords: Great Britain -- Social conditions -- 19th century; London (England) -- Description and travel